Moderating Role of Race/Ethnicity on Associations Between Externalizing Behavior Ratings and School Suspensions - Lorraine R. Blatt; Daniesha Hunter-Rue; Elizabeth Votruba-Drzal (AERA Open)
Inequitable school discipline practices, such as school suspensions, pose a serious threat to children’s development. Prior research has found robust links between children’s externalizing behaviors and school suspensions as well as disproportionalities in suspensions by race/ethnicity. This study extends these literatures using the National Center for Education Statistics’ Early Childhood Longitudinal Study, Kindergarten Class of 1998–99 to examine whether links between children’s externalizing ratings from kindergarten through fifth grade and school suspensions measured in eighth grade differ for children based on race/ethnicity. The analytic sample includes about 9,500 American Indigenous/Alaska Native (2%), Asian (6%), Black (11%), Latinx (18%), Native Hawaiian/Pacific Islander (1%), and white (62%) children. Results showed that ratings of children’s externalizing behaviors are more strongly associated with suspensions for Black children than for Asian, Latinx, and white children, which confirms and extends our knowledge of inequitable discipline practices, thereby reinforcing a need for antiracist solutions.